A perspective on management of Helicoverpa armigera: transgenic Bt cotton, IPM, and landscapes. Issue 3 (5th December 2016) - Downes, Sharon; Kriticos, Darren; Parry, Hazel; Paull, Cate; Schellhorn, Nancy; Zalucki, Myron P
Abstract: Helicoverpa armigera is a major pest of agriculture, horticulture and floriculture throughout the Old World and recently invaded parts of the New World. We overview of the evolution in thinking about the application of area‐wide approaches to assist with its control by the Australian Cotton Industry to highlight important lessons and future challenges to achieving the same in the New World. An over‐reliance of broad‐spectrum insecticides led to Helicoverpa spp. in Australian cotton rapidly became resistant to DDT, synthetic pyrethroids, organophosphates, carbamates and endosulfan. Voluntary strategies were developed to slow the development of insecticide resistance, which included rotating chemistries and basing spray decisions on thresholds. Despite adoption of these practices, insecticide resistance continued to develop until the introduction of genetically modified cotton provided a platform for augmenting Integrated Pest Management in the Australian cotton industry. Compliance with mandatory resistance management plans for Bt cotton necessitated a shift from pest control at the level of individual fields or farms towards a coordinated area‐wide landscape approach. Our take‐home message for control of H. armigera is that resistance management is essential in genetically modified crops and must be season long and area‐wide to be effective. © 2016 Society of Chemical Industry